(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Quality of Work Life is very significant in the context of a commitment to work, motivation and job performance. It is also meant to facilitate the gratification of human needs and goal achievement. Work-life naturally means the life of workers, physical and intellectual, in their work environment in office or factory or field-working. Quality of work life is a Person’s life. It covers a person’s feelings about every dimension of work, including economic rewards and benefits, security, working condition, Organizational and interpersonal relations and their intrinsic meaning in a person’s life. Therefore, we can say Q.W.L. is concerned with improving life at and outside work. The present study is to analyse the Quality of work-life of employees in the Agricultural sector with reference to Ambasamudram Taluk.